2012 US presidential elections: first thoughts - Pecequilo, Cristina Soreanu (2012)
The goal of this article is to present an initial overview of 2012 US Presidential elections, discussing the Republican Party primary election process, suggesting hypothesis regarding the definition of the Republican candidate to the White House and the general challenges facing President Obama´s reelection.